Krüppel-Like Factors 9 and 13 Block Axon Growth by Transcriptional Repression of Key Components of the cAMP Signaling Pathway - Ávila-Mendoza, José; Subramani, Arasakumar; Denver, Robert J. (Frontiers in Molecular Neuroscience, 2020)
Krüppel-like factors (KLFs) are zinc finger transcription factors implicated in diverse biological processes, including differentiation of neural cells. The ability of mammalian neurons to elongate axons decreases during postnatal development in parallel with a decrease in cAMP, and increase in expression of several Klf genes. The paralogous KLFs 9 and 13 inhibit neurite outgrowth, and we hypothesized that their actions are mediated through repression of cAMP signaling. To test this we used the adult mouse hippocampus-derived cell line HT22 engineered to control expression of Klf9 or Klf13 with doxycycline, or made deficient for these Klfs by CRISPR/Cas9 genome editing. We also used primary hippocampal cells isolated from wild type, Klf9-/- and Klf13-/- mice. Forced expression of Klf9 or Klf13 in HT22 changed the mRNA levels of several genes involved with cAMP signaling; the predominant action was gene repression, and KLF13 influenced 4 times more genes than KLF9. KLF9 and KLF13 repressed promoter activity of the protein kinase a catalytic subunit alpha gene in transfection-reporter assays; KLF13, but not KLF9 repressed the calmodulin 3 promoter. Forskolin activation of a cAMP-dependent promoter was reduced after forced expression of Klf9 or Klf13, but was enhanced in Klf gene knockout cells. Forced expression of Klf9 or Klf13 blocked cAMP-dependent neurite outgrowth in HT22 cells, and axon growth in primary hippocampal neurons, while Klf gene knockout enhanced the effect of elevated cAMP. Taken together, our findings show that KLF9 and KLF13 inhibit neurite/axon growth in hippocampal neurons, in part, by inhibiting the cAMP signaling pathway.